First considerations on environmental friendly solutions to protect the Southern Romanian coast (Geo-Eco-Marina, 2019)
The aim of this work is to assess the effect of a nature-based solution for reducing wave heights on the Southern Romanian coast. Apart from investigating the presence of seagrass from the environmental point of view, there is also a need to assess its impact on the coastal hydrodynamics. The impact on the wave heights of a seagrass meadow located on the Southern Romanian coast, has been analyzed by means of a wave model. In this purpose, several numerical simulations have been performed, both for low and average offshore wave conditions, available from a previous wave climate study, which used a 30 years climate data set. A first set of simulations have been performed in the absence of seagrass. Then a seagrass meadow has been added to our grid and the wave model has been run in the same offshore wave conditions. The differences in computed nearshore wave heights reach around 4% for moderate energy waves. These results show that, on the Southern Romanian coast, seagrass could be regarded as an additional measure for nearshore wave attenuation.
Keywords: Southern Romanian coast; seagrass; Zostera noltei; numerical model; simulation; wave height; attenuation